2022
DOI: 10.1186/s13018-021-02898-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tourniquet during total knee arthroplasty when tranexamic acid was used: a meta-analysis of randomized controlled trials

Abstract: Introduction The efficacy of tourniquet use during primary total knee arthroplasty (TKA) is thought to reduce intraoperative blood loss, improve surgical exposure, and optimize cement fixation. Tranexamic acid (TXA) use can decrease postsurgical blood loss and transfusion requirements. This review aimed to appraise the effects of tourniquet use in TKA for patients with tranexamic acid use. Methods A meta-analysis was conducted to identify relevant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 51 publications
0
19
1
11
Order By: Relevance
“…Many studies and metanalyses comparing the efficacy of TXA alone versus tourniquet alone in primary TKA have been published, as have studies comparing the use of TXA and tourniquet combined versus TXA alone in TKA [ 28 - 30 ]. However, studies comparing the two interventions alone and in combination for a total of four study groups (TXA alone, tourniquet alone, both TXA and tourniquet, no intervention) in the context of TKA are lacking in the current anesthesia literature.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies and metanalyses comparing the efficacy of TXA alone versus tourniquet alone in primary TKA have been published, as have studies comparing the use of TXA and tourniquet combined versus TXA alone in TKA [ 28 - 30 ]. However, studies comparing the two interventions alone and in combination for a total of four study groups (TXA alone, tourniquet alone, both TXA and tourniquet, no intervention) in the context of TKA are lacking in the current anesthesia literature.…”
Section: Discussionmentioning
confidence: 99%
“…The performed meta-analysis is not without limitations. The lack of information in many studies on the use of tourniquets and the duration of their use to reduce blood loss however, these limitations in a meta-analysis of tourniquet use in knee arthroplasty found no major differences, in whether or not a tourniquet was used when using TXA during knee arthroplasty [70]. Another limitation may be the lack of knowledge about blood transfusions and blood products that affect hemoglobin levels in addition, the estimation of blood loss was variable as blood loss due to hematomas or tissue extravasation was rarely measured, which could lead to inaccurate results.…”
Section: Discussionmentioning
confidence: 99%
“…1 O único achado a favorecer o uso do torniquete seria uma redução no tempo de cirurgia. 1,11 O objetivo primário deste estudo foi analisar se há uma queda maior nos valores da hemoglobina (Hb) e do hematócrito (Ht) séricos no pós-operatório em pacientes submetidos à cirurgia de ATJ sem a utilização do torniquete. Os objetivos secundários foram analisar se houve diferença em relação ao tempo cirúrgico, aos dias de internação, à necessidade de transfusões, a novas cirurgias para drenagem de hematoma no pós-operatório, à artrofibrose, à deiscência de ferida, às infecções superficial e profunda, à TVP e ao tromboembolismo pulmonar (TEP), ao infarto agudo do miocárdio (IAM) e a óbitos até o sexto mês de pós-operatório.…”
Section: Introductionunclassified
“…The use of a tourniquet in total knee arthroplasty (TKA) is common, as it reportedly improves the visualization of the operative field, reduces intraoperative blood loss, and increases cementation quality. 1,2 Research carried out in 2009 at the American Association of Hip and Knee Surgeons annual meeting to analyze the medical management in TKA showed that a tourniquet was used in up to 58% of the cases. 3 However, many studies point to numerous disadvantages in adopting the tourniquet, including short-term postoperative deficits in knee flexion or extension, 1,4,5 pain and prolonged limb edema, 6 increased wound-related complications, and peripheral nerve injuries, depending on the duration of tourniquet use.…”
Section: Introductionmentioning
confidence: 99%